2023
DOI: 10.3390/nu15061341
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Plant-Based Diet Indices and Metabolic Syndrome in Chinese Adults: Longitudinal Analyses from the China Health and Nutrition Survey

Abstract: Objectives: To investigate the association between a plant-based diet and metabolic syndrome (MetS) among Chinese adults. Methods: Based on the data from the 2004–2015 China Health and Nutrition Survey and the corresponding edition of China Food Composition, we calculated the healthy plant-based diet indices (hPDI) and unhealthy plant-based diet indices (uPDI). The Cox proportional hazards regression model was used to estimate the hazard ratios (HRs) with 95% confidence intervals (CIs) for MetS. Mediation anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 58 publications
3
11
0
Order By: Relevance
“…Our results were compared with those from several studies assessing the relationship between MetS risk and: (1) overall diet, which includes animal-based and plant components, or (2) vegetarian diets. In line with our study, Huo et al [ 40 ] in a cohort study in Chinese adults also revealed no significant relationship between uPDI and MetS, however, they found an inverse association between the hPDI and MetS. They reported that participants in the highest quintile of hPDI score had a 20% lower risk of developing high WC and had a 28% lower risk of developing MetS.…”
Section: Discussionsupporting
confidence: 91%
“…Our results were compared with those from several studies assessing the relationship between MetS risk and: (1) overall diet, which includes animal-based and plant components, or (2) vegetarian diets. In line with our study, Huo et al [ 40 ] in a cohort study in Chinese adults also revealed no significant relationship between uPDI and MetS, however, they found an inverse association between the hPDI and MetS. They reported that participants in the highest quintile of hPDI score had a 20% lower risk of developing high WC and had a 28% lower risk of developing MetS.…”
Section: Discussionsupporting
confidence: 91%
“…According to our knowledge, this is one of the first studies that focused on the effects of COC fasting on MetS and showed promising protective effects. In addition, studies that focus on vegetarian diets [50], such as the Adventist Health Study 2 [51] and the China Health and Nutrition Survey [52], have found that following a more plant-based dietary pattern may have a protective role against MetS, thus further supporting our study findings.…”
Section: Discussionsupporting
confidence: 86%
“…Table 1 describes the characteristics of eligible studies [including 7 cross-sectional studies ( 3 , 5 , 21 , 22 , 24 26 ) and 2 cohort studies ( 4 , 23 )], which included a total of 34,953 participants. The eligible studies have been conducted in Iran ( 5 , 21 , 22 , 26 ), South Korea ( 23 , 24 ), China ( 4 ), Denmark ( 25 ), and the United States ( 3 ). These studies were published between 2020 and 2023.…”
Section: Resultsmentioning
confidence: 99%
“…Dietary intakes were assessed in seven studies using the food frequency questionnaire ( 3 , 5 , 21 24 , 26 ), as well as in two studies using a 24-h recall ( 4 , 25 ). Among the 9 included studies, MetS was defined according to the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) in 3 studies ( 21 23 ), the Joint Interim Statement (JIS) in 4 studies ( 5 , 24 26 ), and the National Chinese guidelines in 1 study ( 4 ). However, 1 study did not provide the method by which MetS was defined ( 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation